Effect of dose and duration of reduction in dietary sodium on blood pressure levels: systematic review and meta-analysis of randomised trials. (24th February 2020) - Huang, Liping; Trieu, Kathy; Yoshimura, Sohei; Neal, Bruce; Woodward, Mark; Campbell, Norm R C; Li, Qiang; Lackland, Daniel T; Leung, Alexander A; Anderson, Cheryl A M; MacGregor, Graham A; He, Feng J
Abstract: Objective: To examine the dose-response relation between reduction in dietary sodium and blood pressure change and to explore the impact of intervention duration. Design: Systematic review and meta-analysis following PRISMA guidelines. Data sources: Ovid MEDLINE(R), EMBASE, and Cochrane Central Register of Controlled Trials (Wiley) and reference lists of relevant articles up to 21 January 2019. Inclusion criteria: Randomised trials comparing different levels of sodium intake undertaken among adult populations with estimates of intake made using 24 hour urinary sodium excretion. Data extraction and analysis: Two of three reviewers screened the records independently for eligibility. One reviewer extracted all data and the other two reviewed the data for accuracy. Reviewers performed random effects meta-analyses, subgroup analyses, and meta-regression. Results: 133 studies with 12 197 participants were included. The mean reductions (reduced sodium v usual sodium) of 24 hour urinary sodium, systolic blood pressure (SBP), and diastolic blood pressure (DBP) were 130 mmol (95% confidence interval 115 to 145, P<0.001), 4.26 mm Hg (3.62 to 4.89, P<0.001), and 2.07 mm Hg (1.67 to 2.48, P<0.001), respectively. Each 50 mmol reduction in 24 hour sodium excretion was associated with a 1.10 mm Hg (0.66 to 1.54; P<0.001) reduction in SBP and a 0.33 mm Hg (0.04 to 0.63; P=0.03) reduction in DBP. Reductions in blood pressure were observed in diverse population subsets examined, including hypertensive and non-hypertensive individuals. For the same reduction in 24 hour urinary sodium there was greater SBP reduction in older people, non-white populations, and those with higher baseline SBP levels. In trials of less than 15 days' duration, each 50 mmol reduction in 24 hour urinary sodium excretion was associated with a 1.05 mm Hg (0.40 to 1.70; P=0.002) SBP fall, less than half the effect observed in studies of longer duration (2.13 mm Hg; 0.85 to 3.40; P=0.002). Otherwise, there was no association between trial duration and SBP reduction. Conclusions: The magnitude of blood pressure lowering achieved with sodium reduction showed a dose-response relation and was greater for older populations, non-white populations, and those with higher blood pressure. Short term studies underestimate the effect of sodium reduction on blood pressure. Systematic review registration: PROSPERO CRD42019140812.